Analysis of the Drama Performance "Janji Senja" by Taofan Nalisaputra Based on Drama Text Structure - Suryaningsih Suryaningsih (Research in Education, Technology, and Multiculture, 2023)
Abstract: This study will discuss the analysis of drama performances. The drama that will be analyzed from this study is entitled "Sunset's Promise" by Taofan Nalisaputra. The analysis of the drama performance in this article is more in-depth regarding the structure of the drama. Some of the drama structures that will be analyzed are the prologue as an introduction, the dialogue sequence of conversations from each character in the scenes, the epilogue is part of the ending, the scene is the way a character plays the role he plays, and the act. Apart from the structure already mentioned, in this article the author also provides an assessment of the strengths and weaknesses of the drama performances studied. There are two main actors in the drama performance staged by theater students, FIB, Unja, namely Sasa as the mother and Natasha Salsabila as the child character. The two main characters played the roles given very professionally. Even so, there are some technical implementations that are less than optimal, such as lighting, shooting, and noisy sound.   Keywords: drama, structure, performance.